Correlation of Serum Cystatin C with Glomerular Filtration Rate in Patients Receiving Platinum-Based Chemotherapy - Ernesta Cavalcanti; Vittoria Barchiesi; Dionigio Cerasuolo; Flaviano Di Paola; Monica Cantile; Sabrina Chiara Cecere; Sandro Pignata; Alessandro Morabito; Raffaele Costanzo; Massimo Di Maio; Francesco Perrone (Analytical Cellular Pathology)
Objectives. Serum cystatin C seems to be an accurate marker of glomerular filtration rate (GFR) compared to serum creatinine. The aim of this work was to explore the possibility of using serum cystatin C instead of serum creatinine to early predict renal failure in cancer patients who received platinum based chemotherapy. Design and Methods. Serum creatinine, serum cystatin C concentrations, and GFR were determined simultaneously in 52 cancer patients received carboplatin-based or cisplatin-based chemotherapy. Serum creatinine was assayed on Cobas C6000-Roche, serum cystatin C assay was performed on AIA 360-Tosoh, and GFR was determined in all patients, before the first cycle of chemotherapy and before the subsequent administrations. Results. In the overall series, for the prediction of a fall of GFR < 80 mL/min/1.73 m2, the AUC of the ROC curve for cystatin C was 0,667 and the best threshold was 1.135 mg/L (sensitivity 90.5%, specificity 61.1%). For a GFR fall < 60 mL/min/1.73 m2, the AUC of ROC curve for cystatin C was 74.3% and the best threshold was 1.415 mg/L (sensitivity 66.7%, specificity 73.2%). Conclusions. Baseline cystatin C values were not able to predict renal failure during subsequent treatment. In conclusion, serum cystatin C is not a reliable early marker to efficiently predict renal failure in patients receiving chemotherapy.